Ser herdeiro de um ancestral que construiu um legado empresarial - Moraes, Josenice Regina Blumenthal de (2011)
Within family business literature, there are currently many issues about succession, the heirs´ skills and, consequently, about the hopes of their long term survival. The realm of these issues is the main justification for this dissertation, which first considered the ensuing research question: are the heirs in family businesses heard? Following this primary research question, the main objective of this dissertation was developed: to comprehend what it means to be the heir of an ancestor that has built up and left behind a business legacy, and how this fact influences the subject´s life; and, more specifically, try to identify in which ways the heirs life is affected based on the subjects own perceptions about this process. In order to achieve these objectives, a qualitative investigation was carried out with an instrumental case study design grounded in the Systemic Approach of the family and in the Three- Dimensional Model of Family Business Development - which tries to differentiate family relationships from the business context. The analysis was also grounded in the Intergenerational Approach, when dealing with legacy and delegations aspects. The subjects of this research were three heirs that were asked by the researcher herself to join this study. Data was drawn from the recordings of semi-structured interviews carried out with the participants, and also from the following instruments applied: the Constructivist Genogram and the Family Time-Line. Preceding individual data analysis, the analysis was first broadly conducted so to, later on, identify differences and similarities amongst the cases. The results reported individual differences concerning the participants unique life stories and similarities that are constituent of the heir-phenomenon and its influences in their life, which in turn, can be generalized. This dissertation points out paths for further in-depth scientific research, specifically in Brazilian academia, that can help provide further comprehension of the heir-phenomenon within our country s peculiarities